Cyclooxygenase-2 expression in gastroenteropancreatic neuroendocrine tumors - (:unkn) unknown (H G E UPDATE MEDICAL PUBLISHING S A, 2007)
Background/Aims: The aim of this multicenter study was to investigate cyclooxygenase-2 protein expression in gastroenteropancreatic neuroendocrine tumors and to examine the relationship to various clinicopathological parameters. Methodology: Thirty-seven gastroenteropancreatic neuroendocrine tumor specimens were analyzed immunohistochemically. Correlations between expression and some parameters such as age, sex, tumor size, location, presence of multiple neuroendocrine tumor, lymphatic/vascular/muscularis propria invasion and lymph node metastases were evaluated. Results were interpreted as significant if p < 0.05. Results: Mean age of patients (15 men/22 women) was 52 +/- 17. Tumor size varied between 0.1 and 12cm. (mean; 3.17 +/- 3.29cm). Expression was detected in 75% of cases and in 92% of gastric neuroendocrine tumors. Expression in mixed endocrine and non-endocrine carcinomas was found to be significantly higher than in well-differentiated 'neuroendocrine tumors and carcinomas (p=0.016). A relationship was observed between overexpression and lymphatic and vascular invasion (p=0.029). However, no significant correlation was found between expression and sex, tumor location, size; muscularis propria invasion and lymph node metastasis. Conclusions: Cyclooxygenase-2 expression may play a role in the evolution of gastroenteropancreatic neuroendocrine tumors. However, further studies are necessary to determine the importance of this role, prognostic relevance and whether cyclooxygenase isoenzyme can be a target for treatment in these tumors.
Keywords: cyclooxygenase-2; non-steroidal; anti-inflammatory drugs; neuroendocrine tumors; NONSTEROIDAL ANTIINFLAMMATORY DRUGS; HUMAN GASTRIC-CANCER; CELL-CYCLE ARREST; COLORECTAL-CANCER; CLINICOPATHOLOGICAL FEATURES; COX-2 INHIBITION; BREAST-CANCER; COLON-CANCER; CARCINOMA; GROWTH